Psychosocial work environment stressors for school staff during the COVID-19 pandemic: Barriers and facilitators for supporting wellbeing - Rolf, Liz R.; Vestal, Liz; Moore, Ashley C.; Lobb Dougherty, Nikole; Mueller, Nancy; Newland, Jason G. (Frontiers in Public Health, 2023)
Introduction After periods of remote and/or hybrid learning as a result of the COVID-19 global pandemic, the return to in-person learning has been beneficial for both students and teachers, but it has not been without challenges. This study was designed to assess the impact of the return to in-person learning on the school experience, and efforts made to ease the transition in furthering a positive in-person learning environment. Materials and methods We conducted a series of listening sessions with 4 stakeholder groups: students (n=39), parents (n=28), teachers/school staff (n=41), and a combination of listening sessions and semi-structured interviews with building level and district administrators (n=12), focusing on in-school experiences during the 2021-2022 school year amidst the COVID-19 pandemic. A primarily deductive qualitative analysis approach was employed to code the data followed by a primarily inductive thematic analysis, followed by thematic aggregation, thus providing depth and identification of nuances in the data. Results Three main themes emerged around school staff experiences: 1) increased levels of stress and anxiety manifested in key ways, including students’ challenges with personal behavior management contributing to increased aggression and staff shortages; 2) school staff described key contributors to stress and anxiety, including feeling excluded from decision making and challenges with clear and consistent communication; and 3) school staff described key facilitators that supported their management of anxiety and stress, including adaptability, heightened attention and resources to well-being, and leveraging interpersonal relationships. Discussion School staff and students faced significant stress and anxiety during the 2021-2022 school year. Further exploration and identification of approaches to mitigate key contributors to increased stress and anxiety for school staff, along with increased opportunities for implementing key facilitators that were identified as important in managing and navigating the increased stress and anxiety offer valuable opportunities for helping to create a supportive work environment for school staff in the future.